Early evolution of BRAFV600 status in the blood of melanoma patients correlates with clinical outcome and identifies patients refractory to therapy. Issue 3 (June 2018) - Gonzalez-Cao, Maria; Mayo de las Casas, Clara; Jordana Ariza, Nuria; Manzano, Jose L.; Molina-Vila, Miguel Á.; Soriano, Virtudes; Puertolas, Teresa; Balada, Ariadna; Soria, Ainara; Majem, Margarita; Montagut, Clara; Muñoz, Eva; et al.
Abstract : Serial analysis of BRAF mutations in circulating-free DNA (cfDNA) could be of prognostic value in melanoma patients. We collected blood samples from 63 advanced BRAFV600E/K melanoma patients and determined BRAFV600E/K status in cfDNA using a quantitative 5′-nuclease PCR-based assay. Levels of BRAF mutation in pre-cfDNAs were associated significantly with tumour burden, progression-free survival and overall survival. Changes in BRAF status in cfDNA after initiation of treatment (early-cfDNA) had a significant correlation with outcome. In patients with persistent BRAF mutations ( n =12), progression-free survival and overall survival were 3.5 months [95% confidence interval (CI): 1.6–4.6] and 5.3 months (95% CI: 3.4–8.1) compared with 16.6 months (95% CI: 8.2–22.3) and 21.9 months (95% CI: 10.2–NR) in patients with BRAF negativization ( n =16), and 15.1 months (95% CI: 2.3–NR) and NR (95% CI: 5.1–NR) in patients who maintained their initial negative status ( n =12) ( P <0.0001). The median duration of response in patients with radiological response, but persistence of BRAFV600 in early-cfDNA ( n =5) was 4 months. Our study indicates that serial BRAF testing in the blood of advanced melanoma identifies patients refractory to therapy. Abstract : Supplemental Digital Content is available in the text.